The importance of the zero budget as a mechanism for the governance of public spending- A sample study for a group of municipalities in the state of M'sila - bouguerra, Fouad; bissar, Abdelmoutaleb (Journal of Research in Finance and Accounting, 2026)
This study aims to highlight the importance of the zero budget and its contribution to the success of the public spending governance process for a group of municipalities in the state of M'sila. The descriptive analytical method was relied on in the study, after distributing the questionnaire to 52 employees for the purpose of data collection and analysis. And its analysis was concluded that (Z.B.B) it contributes to the success of resource allocation, and raises the efficiency of the control and administrative apparatus of the municipalities under study.